2015
DOI: 10.1371/journal.pone.0126266
|View full text |Cite
|
Sign up to set email alerts
|

Severe Adverse Maternal Outcomes among Women in Midwife-Led versus Obstetrician-Led Care at the Onset of Labour in the Netherlands: A Nationwide Cohort Study

Abstract: ObjectiveTo test the hypothesis that it is possible to select a group of low risk women who can start labour in midwife-led care without having increased rates of severe adverse maternal outcomes compared to women who start labour in secondary care.Design and MethodsWe conducted a nationwide cohort study in the Netherlands, using data from 223 739 women with a singleton pregnancy between 37 and 42 weeks gestation without a previous caesarean section, with spontaneous onset of labour and a child in cephalic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…9,10 Studies in several countries have shown that midwifery-led care and alternative birth places are associated with better maternal outcomes. 2,5,[11][12][13] Other studies have emphasized the importance of the proximity of a hospital in case of need. 14,15 Midwifery-led birth centers within hospitals have been created, allowing for quick emergency interventions, thanks to the immediate availability of doctors and operating theaters.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Studies in several countries have shown that midwifery-led care and alternative birth places are associated with better maternal outcomes. 2,5,[11][12][13] Other studies have emphasized the importance of the proximity of a hospital in case of need. 14,15 Midwifery-led birth centers within hospitals have been created, allowing for quick emergency interventions, thanks to the immediate availability of doctors and operating theaters.…”
Section: Introductionmentioning
confidence: 99%
“…Midwife-led birth settings have been associated with a lower rate of severe adverse maternal morbidity [11]. Additionally, international studies showed a significantly lower risk of episiotomy [12, 13], pharmacological pain management [1215], assisted vaginal birth [12, 13], caesarean section [12, 13], and augmentation of labour [1215] in birth settings other than obstetric units, although in one study no difference in rate of instrumental births was found [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent Dutch study among 743.070 low risk women showed similar rates of perinatal morbidity and mortality among planned home and planned midwife-led hospital births [17]. Another study showed no increased rates of severe maternal morbidity among planned home births [11]. Less is known about differences in interventions and other maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all indications for referral are registered in Perined. For example, in a study into severe acute maternal morbidity, 27% of women with a previous caesarean section had no record of this risk factor in Perined . Again, this can lead to problems in the definition of the numerator and denominator .…”
mentioning
confidence: 99%
“…If risk levels in study groups are not equal, a comparison of outcomes provides little information on a possible difference in quality of care if confounding cannot be adequately controlled for. For example, lower rates of severe acute maternal morbidity have been found among women who start labour in midwife‐led versus in obstetrician‐led care (group a versus b) . To a large extent, this is most probably attributable to the fact that women in midwife‐led care have fewer obstetric risk factors, rather than due to the care women receive in either setting.…”
mentioning
confidence: 99%